Blacasset, “Se·l mals d’amor m’auzi ni m’es noisens” (BdT 96.10a); Pujol, “Dieus es amors e verais salvamens” (BdT 386.2); Alaisina ~ Carenza, “Na Carenza al bel cors avenenç” (BdT 12.1 = 108.1) - Paolo Di Luca (Lecturae Tropatorum, 2012)
This paper provides a new critical edition of “Se·l mals d’amor m’auzi ni m’es noisens” by Blacasset and “Dieus es amors e verais salvamens by Pujol”. These two poets discuss a topic that is entirely new to Occitan lyric poetry: two young women about to enter a convent. While Blacasset expresses sadness about their choice of life in a convent, using elements of the funeral lament, Pujol praises it and believes it to be the only remedy for the corruption of the world. The tenso between women “Na Carenza al bel cors avenenç” seems to be conceived as a parody of this lyric debate: in the dialogue Alaisina and Yselda, who have doubts about becoming mothers, ask Na Carenza whether it is better to stay virgins or to marry; the latter advises them, in cryptic terms that are difficult to interpret, to become nuns, thereby gaining a husband (God) but not children. I will suggest that the question of female authorship for this text be reconsidered, while proposing a new interpretation in the light of the lively debate in the medieval period about the suitability and prerogatives of virginity.